O Programa NEPSO e suas contribuições para o currículo do Ensino Médio nas escolas públicas paulistas - Leite, Rita Carmona Moreira (2015)
The central objective of this research is to evaluate the program Nossa Escola Pesquisa sua Opinião (NEPSO) [Our School Researches Your Opinion), more specifically its 2013 edition, in the segment High School. The investigation of the program in this education segment is justified mainly by the current context of Brazilian High School: high dropout and failure rates as well as poor results in several evaluations undertaken. Within the context of these results, High School has just had its Curriculum Guidances approved (2012), a fact that has allowed a large multiplicity of curriculum reformulation proposals in this segment, which intend to overcome, among others, the historical conflict between professional and propaedeutic education that has permeated all history of High School implementation in Brazil. Therefore, this research, from the investigation of a program developed over ten years in this segment, aims at identifying what are the main apprenticeships developed by young people and participant teachers, besides verifying the curriculum contributions for the development of this methodology in two experienced schools. In the light of theoretical backgrounds used, data and information collected bring relevant contributions to the international debate regarding the curriculum issue for High School in order to ensure the development of more contextualized curriculums and propose methodological alternatives that may mobilize the interest of young people in building up knowledge and valuing the expertise produced by themselves, according to some of the principles already described on the National Curriculum Guidelines for High School. Once it is an educational research composed by a variety of factors and visions on a complex reality, the methodological approach chosen for this investigation is the qualitative one, an option that has made possible the use of several investigation procedures and analysis of reality. Thus, documental analyses have been developed, along with in-depth interviews with young people, teachers, school principals and a professional responsible for the pedagogical coordination of the program. Furthermore, it has been possible to develop the observation and the follow up of both formation meetings and results presentation. All these elements have offered a diversified material of analysis, a fact that has favored the construction of questioning and indicative elements capable of increasing both reflections and the development of curriculum proposals for the improvement of public education quality in Brazilian High Schools